PENGARUH PEMBERIAN JUS Aloe vera TERHADA PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI PUSKESMAS BUMIAYU KECAMATAN BUMIAYU KABUPATEN BREBES - Tri Sumarni; Pramesti Dewi (Universitas Harapan Bangsa Purwokerto, 2012)
Diabetes mellitus (DM) or diabetes, including category degenerative diseases harmfulto humans at this time. One factor that may help lower blood sugar levels is to therapyAleovera juice (aloe vera), its content can lower blood sugar levels in addition to the need forinsulin / medication which contain many chemicals.This study aimed to determine the effectof aloe vera juice to decrease blood sugar levels in patients with Type II diabetes in BrebesDistrict Health Clinics Brits. This study used an experimental design with pre and post testapproach to design. Population / sample is non probability sampling with accidentalsampling method at the district health center. Brits as many as 25 people. Cheklist datacollection refers to blood sugar levels. Analysis of data using statistical test throughcomparative hypothesis is to test a population-shaped normal distribution comparison usingpaired T-test. Statistical test results on the respondents treated p value = 0.0002, There is asignificant relationship between the first measurement with the second measurement after agiven treatment administration of Aloe Vera juice to decrease blood sugar levels in patientswith diabetes mellitus type II. It was therefore concluded there is a significant differencebetween the levels of sugar in the first measurement with the second measurement. From thedata obtained the average sugar content 278.52 mg / dl, defiasi 51.23 mg / dl, and after giventhe aloe vera juice obtained an average sugar content 224.56 mg / dl highest sugar levels 314mg / dl and lowest 152 mg / dl with a standard deviation of 49.37 mg / dl. It is concluded thatadministration of Aloe Vera juice can lower blood glucose levels in diabetic patients. Keywords: Diabetes Mellitus Type II, Aloe Vera Juice, Blood Sugar Levels.